Maternal pre-pregnancy weight and externalising behaviour problems in preschool children: a UK-based twin study. Issue 10 (14th October 2014) - Antoniou, Evangelia E; Fowler, Tom; Reed, Keith; Southwood, Taunton R; McCleery, Joseph P; Zeegers, Maurice P
Abstract : Objective: To estimate the heritability of child behaviour problems and investigate the association between maternal pre-pregnancy overweight and child behaviour problems in a genetically sensitive design. Design: Observational cross-sectional study. Setting: The Twins and Multiple Births Association Heritability Study (TAMBAHS) is an online UK-wide volunteer-based study investigating the development of twins from birth until 5 years of age. Participants: A total of 443 (16% of the initial registered members) mothers answered questions on pre-pregnancy weight and their twins' internalising and externalising problems using the Child Behavior Checklist and correcting for important covariates including gestational age, twins' birth weight, age and sex, mother's educational level and smoking (before, during and after pregnancy). Primary outcomes: The heritability of behaviour problems and their association with maternal pre-pregnancy weight. Results: The genetic analysis suggested that genetic and common environmental factors account for most of the variation in externalising disorders (an ACE model was the most parsimonious with genetic factors (A) explaining 46% (95% CI 33% to 60%) of the variance, common environment (C) explaining 42% (95% CI 27% to 54%) and non-shared environmental factors (E) explaining 13% (95% CI 10% to 16%) of the variance. For internalising problems, a CE model was the most parsimonious model with the common environment explaining 51% (95% CI 44% to 58%) of the variance and non-shared environment explaining 49% (95% CI 42% to 56%) of the variance. Moreover, the regression analysis results suggested that children of overweight mothers showed a trend (OR=1.10, 95% CI 0.58% to 2.06) towards being more aggressive and exhibit externalising behaviours compared to children of normal weight mothers. Conclusions: Maternal pre-pregnancy weight may play a role in children's aggressive behaviour.